Commercialization of academic patents in Chinese universities: Antecedents and spatial spillovers - Jiafeng Gu (Heliyon, 2023)
The commercialization of academic patents is a basic means for universities to promote economic growth and upgrade the industrial innovation of enterprises. However, among developing countries, the commercialization rate of university patents is generally low. This study utilizes data from 65 universities which are directly under the Ministry of Education of China to analyze the influencing factors and mechanisms of academic patent commercialization. The findings show that the proportion of associate professors, the size of service staff transforming research and development achievement, and the proportion of basic research funding in universities are positively correlated with the commercialization rate of university patents. In addition, these factors indirectly affect the commercialization of university patents by affecting neighboring universities; that is, there are spatial spillover effects in the commercialization of university patents between neighboring universities. These empirical results indicate that universities can promote the commercialization of university patents by optimizing the structure of faculty, developing the R&D achievement transformation service staff team, and strengthening investment in basic research.